2011
DOI: 10.1152/jn.00886.2010
|View full text |Cite
|
Sign up to set email alerts
|

Representation of limb kinematics in Purkinje cell simple spike discharge is conserved across multiple tasks

Abstract: Encoding of movement kinematics in Purkinje cell simple spike discharge has important implications for hypotheses of cerebellar cortical function. Several outstanding questions remain regarding representation of these kinematic signals. It is uncertain whether kinematic encoding occurs in unpredictable, feedback-dependent tasks or kinematic signals are conserved across tasks. Additionally, there is a need to understand the signals encoded in the instantaneous discharge of single cells without averaging across … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
123
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(133 citation statements)
references
References 62 publications
10
123
0
Order By: Relevance
“…Functional activity in the cerebellum during repeated foot movements agrees with the cerebellar homunculus within the anterior lobe [54]. Along with the study of Hewitt and colleagues (2011) our results suggest that the ability to move as fast as possible is bound to the capability of generating highest possible discharge rates in a certain population of Purkinje cells [12]. Due to the concept of spatial summation at the dendritic tree, which in part underlies volumetric differences [55], it is likely that this ability is manifested in a neuroanatomical correlate of increased grey matter volume in the cerebellar anterior lobe.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Functional activity in the cerebellum during repeated foot movements agrees with the cerebellar homunculus within the anterior lobe [54]. Along with the study of Hewitt and colleagues (2011) our results suggest that the ability to move as fast as possible is bound to the capability of generating highest possible discharge rates in a certain population of Purkinje cells [12]. Due to the concept of spatial summation at the dendritic tree, which in part underlies volumetric differences [55], it is likely that this ability is manifested in a neuroanatomical correlate of increased grey matter volume in the cerebellar anterior lobe.…”
Section: Discussionsupporting
confidence: 85%
“…Indeed, the cerebellum is characterised as the neural site which encodes speed information and provides a forward internal model to plan or control movements in a kinematic framework [10]. According to this, several animal studies observed correlations between discharge rate of Purkinje cells and movement velocity [11], [12]. In humans, it could be shown that patients with cerebellar lesions are not able to generate fast arm speeds compared to healthy controls [13].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we evaluated Purkinje cell firing during random tracking and verified that position, velocity and speed of the limb (denoted in Figure 1B by the C subscripted variables) were statistically independent (Hewitt et al, 2011). For a large majority of Purkinje cells, simple spike firing is modulated in relation to these kinematic parameters.…”
Section: Cerebellum and Motor Domainmentioning
confidence: 85%
“…The first is rate coding in which the simple spike frequency is varied. It has been shown that the Purkinje simple spike frequency is correlated with arm kinematic and dynamic variables (Albus 1971;Dean et al 2010;Ebner et al 2011;Hewitt et al 2011;Lisberger 2009;McElvain et al 2010;Pasalar et al 2006). The second is spatiotemporal coding where the spike synchrony between multiple Purkinje cells is the mechanism for propagation of information.…”
mentioning
confidence: 99%